2021
DOI: 10.1186/s12889-021-11642-7
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring sustainability of polio immunization in health system transition: lessons from the polio eradication initiative in Indonesia

Abstract: Background Sustaining an effective evidence-based health intervention will maximize its impact on public health. Political and governmental reforms impacted on immunization program sustainability both positively and negatively. This study aims to explore the sustainability of polio immunization in a decentralized health system taking lessons learned from a polio eradication initiative in Indonesia. Methods We collected qualitative data through in-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…Funding priorities in maternal health can differ substantially across districts, impacting the supply of key inputs to EMTCT programs. This phenomenon has also been observed in a previous study on immunisation programs in the country [37].…”
Section: Discussionsupporting
confidence: 86%
“…Funding priorities in maternal health can differ substantially across districts, impacting the supply of key inputs to EMTCT programs. This phenomenon has also been observed in a previous study on immunisation programs in the country [37].…”
Section: Discussionsupporting
confidence: 86%
“…The NCD-PCP does not have a specific budget line, and despite the increase in the total share of health from the GDP, the disproportionate share of NCDs from the health budget has resulted in funding instability (24). In a study by Azizatunnisa, the health budget was allocated only to treatment and hospital facilities due to the local government's negligence of preventive measures and inadequate infrastructure in primary healthcare, which affected the sustainability of the vaccination program (25).…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The reallocated budget was the health operational budget that was originally intended for mass-gathering activities such as workshops and posyandu. 7 A study reported that this reallocation was implemented at all puskesmas in East Lombok District, West Nusa Tenggara Province. In puskesmas in Selong East Lombok, before the reallocation, the budget for essential services was 64% of the total puskesmas budget per year.…”
Section: Resource Diversionmentioning
confidence: 99%
“…With GPEI's assistance, Indonesia has built the capacity for effective polio outbreak response, including the ability to conduct field, virological, and epidemiological investigations and have an acute flaccid paralysis (AFP) surveillance system. 7 The Southeast Asia region, including Indonesia, has been certified as polio-free since 2014. Currently, every country in the world has been polio-free except Afghanistan and Pakistan.…”
Section: Introductionmentioning
confidence: 99%